Surgical fixation of fractures of the distal radius within 2 weeks reduces postoperative finger stiffness. (January 2021) - Ashdown, Thomas; Morris, James; Mckeon, Sean; Clough, Oliver T.; Little, Max; Anakwe, Raymond E.
Locked anterior plating remains the most common form of surgical fixation for displaced fractures of the distal radius. We hypothesized that delayed surgical fixation later than 2 weeks after injury contributes to poorer patient outcomes for patients with displaced or intra-articular fractures of the distal radius. We conducted a retrospective cohort study of 158 patients who underwent locked anterior plating for an intra-articular or displaced fracture of the distal radius using multiple regression analysis to identify any relationship between patient, injury or treatment factors with the patient-rated wrist and hand evaluation score or finger and wrist stiffness. There was no significant correlation between timing of surgery and functional scores. A delay in time to surgery of more than 2 weeks did correlate significantly with increased finger and thumb stiffness. However, this relationship was not seen for wrist stiffness. Our study supports the consensus that early recovery and function is facilitated by surgical fixation within 2 weeks and that delayed fixation beyond this may contribute to protracted finger stiffness. Level of evidence: IV